Impact of Climate Change on The Export of Palm Oil, Coffee Beans, and Cocoa Beans - Purbantoro, Bhirawa Anoraga; Anggraeni, Lukytawati; Pasaribu, Syamsul Hidayat (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Climate change is believed to impact the economy of a country. The production of food crop commodities is one of the activities that is negatively impacted by the climate change and the volume of exports. Palm oil, coffee beans, and cocoa beans are the agricultural sector's leading commodities with high competitiveness in international markets and contribute significantly to exporting countries' economies. This research aims to determine the impact of climate change (changes in the annual average temperature and total annual precipitation) on the exports of the three commodities. This study uses secondary data from various sources. The data were analyzed using panel data regression analysis. The result shows that temperature and precipitation variables have different effects on the three commodities. Temperature and precipitation variables have a significant adverse impact on coffee bean exports. In contrast, temperature and precipitation variables positively affect palm oil exports. Meanwhile, for cocoa beans, only the precipitation variable positively affects export. Adaptation action by introducing climate varietas is important to maintain future exports of those commodities. Keywords: precipitation, panel data, leading commodities, climate change, agricultural sector's